2001
DOI: 10.1038/labinvest.3780376
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplasia of Alveolar Neuroendocrine Cells in Rat Lung Carcinogenesis by Silica with Selective Expression of Proadrenomedullin-Derived Peptides and Amidating Enzymes

Abstract: SUMMARY:Pulmonary neuroendocrine (NE) cells are found as clusters called neuroepithelial bodies (NEBs) or as single cells scattered in the respiratory epithelium. They express a variety of bioactive peptides, and they are thought to be the origin of NE lung tumors. Proadrenomedullin N-terminal 20 peptide (PAMP) is a peptide derived from the same precursor as adrenomedullin (AM). AM and PAMP are C-terminally amidated during their processing by a well-characterized amidating enzyme, peptidylglycine alpha-amidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Experimentally induced hyperplasia of PNECs has been observed to occur in response to various toxic gases or carcinogenic stimuli [37]. Depending on the specific stimulus, the proliferative effect may be specifically restricted to a certain airway region [38,39]. PNEC proliferation was also seen in a number of non-neoplastic human lung diseases [37].…”
Section: Discussionmentioning
confidence: 98%
“…Experimentally induced hyperplasia of PNECs has been observed to occur in response to various toxic gases or carcinogenic stimuli [37]. Depending on the specific stimulus, the proliferative effect may be specifically restricted to a certain airway region [38,39]. PNEC proliferation was also seen in a number of non-neoplastic human lung diseases [37].…”
Section: Discussionmentioning
confidence: 98%
“…In neuroendocrine cells of the larynx and trachea, serotonin could not be demonstrated, whereas in the lung, serotonin-containing cells were seen. (Adriaensen et al 2001;Boorman, Morgan, and Uraih 1990;Dungworth, Ernst, et al 1992;Dungworth et al 2001;Elizegi et al 2001;Gopinath, Prentice, and Lewis 1987;Haworth et al 2007;Karube et al 1989;Kasacka and Sawicki 2004;Kerns et al 1983;Larson et al 2004;Lauweryns and Van Ranst 1988;Lauweryns et al 1987;D. Lewis 1991;Luts et al 1991;Maronpot et al 1986;McBride et al 1990;Montuenga et al 1992;Pack, Al-Ugaily, and Morris 1981;Rehm and Kelloff 1991;Shimosegawa and Said 1991;Takahashi, Iwasaki, and Ide 1985;Van Lommel 2001;Van Lommel et al 1999) Hyperplasia with Cellular Atypia (Dysplasia): Larynx, Trachea, Bronchi, Bronchioles Pathogenesis/cell of origin: Proliferation of respiratory epithelium, or submucosal glands.…”
Section: Larynx Trachea Bronchi and Bronchiolesmentioning
confidence: 96%
“…[69][70][71][72][73] The role of growth factors and cytokines in the pathogenesis of silica-induced lung carcinogenesis has been the object of earlier studies. [20][21][22][74][75][76][77] It was shown that hyperplastic type II cells present in this model are sites of active production and secretion of TGF-b1. 21,76 In rat alveolar cells in culture, silica treatment induced a dramatic secretion of TGF-b1.…”
Section: Discussionmentioning
confidence: 99%